Spontaneous Regression of Epithelioid Angiosarcoma in a Young Woman - Hori, Suya; Hirose, Takanori; Kobayashi, Kazuyuki; Tamura, Daisuke; Sakai, Yasuhiro; Nakata, Kyosuke; Itoh, Tomoo; Nishimura, Yoshihiro; Tachihara, Motoko; Kamiryo, Hiroshi (Internal Medicine, 2017)
A 20-year-old Japanese woman with a history of pulmonary atresia was referred to our hospital after the detection of an abnormal mass in the right lung and mediastinal lymphadenopathy. A cytological specimen obtained by transbronchial brushing indicated that the pathological diagnosis was non-small cell lung cancer. During the follow-up period, the tumor spontaneously regressed. At four months after the diagnosis, she experienced sudden bleeding from the small intestine. The histological characteristics of the small intestine tumor were compatible with the cytological characteristics of the lung tumor. Detailed immunohistochemical analyses led to a final diagnosis of epithelial angiosarcoma of the small intestine, which might have formed metastatic lesions in the lung.